2018
DOI: 10.1016/j.molmet.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of estrogen receptor alpha induces beiging of adipocytes

Abstract: ObjectivesBrown adipose tissue (BAT) and BAT-like adipose tissues, referred to as ‘beige’ adipose tissues uncouple respiration from ATP synthesis via uncoupling protein one (UCP-1). There is a sexual dimorphism with respect to beige and BAT tissues; pre-menopausal women have more BAT and are more sensitive to BAT activation than men or postmenopausal women. We hypothesized selective activation of adipose tissue estrogen receptor alpha (ERα) induces beiging of WAT through induction of lipolysis mediated by adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 45 publications
0
42
1
Order By: Relevance
“…OCR was measured every 8.5 min for 400 min. To demonstrate the effect of lipolysis we added 20 μM ATGL inhibitor Atglinstatin (Sigma-Aldrich) as described previously [ 51 ], with 0.5 AM6545 or 0.5 mM RIM. The real-time measurements were performed for 400 min.…”
Section: Methodsmentioning
confidence: 99%
“…OCR was measured every 8.5 min for 400 min. To demonstrate the effect of lipolysis we added 20 μM ATGL inhibitor Atglinstatin (Sigma-Aldrich) as described previously [ 51 ], with 0.5 AM6545 or 0.5 mM RIM. The real-time measurements were performed for 400 min.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this observation, oestrogens have recently been demonstrated to enhance thermogenesis in brown adipose tissue and to promote beiging of white adipocytes. Indeed, in vitro and in vivo approaches have demonstrated that selective activation of ERα induces adipose tissue beiging through induction of AMP-activated protein kinase (AMPK) and adipose triglyceride lipase (ATGL)-mediated lipolysis, resulting in NEFA generation and uncoupling protein 1 (UCP-1) activation [29]. Finally, as revealed by 18 F-fluoro-2-deoxy-d-glucose ( 1 8 F-FDG) positron-emission tomography-computed tomography (PET-CT) scanning, brown adipose tissue is better preserved and more metabolically active in women than in men, thus contributing to enhanced energy expenditure in the former [30,31].…”
Section: Biological Sex As a Determinant Of Energy Balance And Body Cmentioning
confidence: 99%
“…Previous studies have shown that estrogen plays a role as an active substance leading to lipolysis and thereby offering protection against obesity development [ 36 , 37 ]. Thus, it is important to investigate whether estrogen deficiency is the primary factor in the development of hypothalamic inflammation revealed in the postmenopausal model or the alteration of metabolites associated with an expansion of fat tissues is also responsible for the same.…”
Section: Discussionmentioning
confidence: 99%